A new species of white-spotted moray eel, Gymnothorax smithi (Muraenidae: Muraeninae) from deep waters of Arabian Sea, India - Sumod, K. S.; Mohapatra, Anil; Sanjeevan, V. N.; Kishor, T. G.; Bineesh, K. K. (Zootaxa, 2019)
A new species of white-spotted moray eel Gymnothorax smithi sp. nov. is described based on three specimens collected from the southeastern Arabian Sea, India. This is the first deep water report of a moray eel from Indian waters from 200 m depth. This new species is distinguishable from its congeners by the following combination of characters: greyish brown body overlain with white spots of irregular shape, dorsal-fin origin anterior to gill opening, anus positioned slightly behind the mid-point of the body, serrated teeth and a unique vertebral count 3–5 /57/130–132. [Zoobank URL: urn:lsid:zoobank.org:act:9554CE07-E9E7-4B4F-95CD-54F2BB26FF28]